Essays on economic consequences of complex policies and fertility desires: Evidence from survey panels, registers and behavioral interventions - Sofie Cairo (University of Copenhagen, Department of Economics, 2020)
This PhD dissertation consists of three self-contained chapters. The first chapter studies the role of fertility preferences of young women for their education, family formation and labor market outcomes. The second and third chapter share a common focus on the complexity of public policies, such as sanctions and work requirements, for job search and labor market outcomes of benefit recipients. The last chapters share a common methodology relying on evidence from recent large-scale field experiments among Danish jobseekers conducted in collaboration with The Danish Agency for Labor Market and Recruitment. [...]
Keywords: 330; Fertilität; Frauen; Erwerbsverlauf; Bildungsertrag; Arbeitsuche; Arbeitslosenversicherung; Aktivierende Arbeitsmarktpolitik; Dänemark